Emerging role of non-coding RNAs in glucose metabolic reprogramming and chemoresistance in colorectal cancer - Yan, Shushan; Wang, Shufeng; Wang, Xinyi; Dai, Wenqing; Chu, Jinjin; Cheng, Min; Guo, Zhiliang; Xu, Donghua (Frontiers in Oncology, 2022)
Metabolic reprogramming plays a critical role in colorectal cancer (CRC). It contributes to CRC by shaping metabolic phenotypes and causing uncontrolled proliferation of CRC cells. Glucose metabolic reprogramming is common in carcinogenesis and cancer progression. Growing evidence has implicated the modifying effects of non-coding RNAs (ncRNAs) in glucose metabolic reprogramming and chemoresistance in CRC. In this review, we have summarized currently published studies investigating the role of ncRNAs in glucose metabolic alterations and chemoresistance in CRC. Elucidating the interplay between ncRNAs and glucose metabolic reprogramming provides insight into exploring novel biomarkers for the diagnosis and prognosis prediction of CRC.